Host- and microbe determinants that may influence the success of S. aureus colonization - Johannessen, Mona; Sollid, Johanna E.; Hanssen, Anne M. (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus may cause serious skin and soft tissue infections, deep abscesses, endocarditis, osteomyelitis, pneumonia and sepsis. S. aureus persistently colonizes 25-30% of the adult human populations. S.aureus carriers have an increased risk for infections caused by the bacterium. The major site of colonization is the nose, i.e. the vestibulum nasi which is covered with ordinary skin and hair follicles. Several host- and microbe determinants are assumed to be associated with colonization. These include presence and expression level of bacterial adhesins which can adhere to various proteins in the extracellular matrix or on the cellular surface of human skin. The host expresses several antimicrobial peptides and lipids. The level of β-defensin-3, free sphingosine and cis-6-hexadecenoid acid are found to be associated with nasal carriage of S. aureus. Other host factors found to be associated with carriage are certain polymorphisms in Toll-like receptor 2, mannose-binding lectin, C-reactive protein, glucocorticoid- and vitamin D receptor. Other putative determinants for carriage include genetic variation and expression of MSCRAMMS and their interaction partners, as well as variation among humans in the ability of recognizing and responding appropriate to the bacteria. In addition, the available microflora may influence the success of S. aureus colonization.